Synchronous records of pCO2 and Δ14C suggest rapid, ocean-derived pCO2 fluctuations at the onset of Younger Dryas - Steinthorsdottir, M.; de Boer, A.M.; Oliver, K.I.C.; Muschitiello, F.; Blaauw, M.; Reimer, P.J.; Wohlfarth, B. (Quaternary Science Reviews, 2014)
Just before the onset of the Younger Dryas (YD) cold event, several stomatal proxy-based pCO2 records have shown a sharp increase in atmospheric CO2 concentration (pCO2) of between ca 50 and 100 ppm, followed by a rapid decrease of similar or even larger magnitude. Here we compare one of these records, a high-resolution pCO2 record from southern Sweden, with the IntCal13 record of radiocarbon (Δ14C). The two records show broadly synchronous fluctuations at the YD onset. Specifically, the IntCal13 record documents decreasing Δ14C just before the YD onset when pCO2 peaks, consistent with a source of “old” CO2 from the deep ocean. We propose that this fluctuation occurred due to a major ocean flushing event. The cause of the flushing event remains speculative but could be related to the hypothesis of the glacial ocean as a thermobaric capacitor. We confirm that the earth system can produce such large multi-decadal timescale fluctuations in pCO2 through simulating an artificial ocean flushing event with the GENIE Earth System Model. We suggest that sharp transitions of pCO2 may have remained undetected so far in ice cores due to inter-firn gas exchange and time-averaging. The stomatal proxy record is a powerful complement to the ice core records for the study of rapid climate change.